Odpowiedzi

Najlepsza Odpowiedź!
2010-03-20T19:48:48+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8
b)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8
c)3(x-1)=0
3x-3=0
3x=0+3
3x=3/:3
x=1
d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:(-6)
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=1,5
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5
27 4 27
2010-03-20T19:49:21+01:00
A) 4x-3x=5+3
x=8
b) 5x+3x=7-2
8x=5
x= 5/8
c) 3x-3=0
3x=0+3
3x=3
x=1
d) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:(-6)
x=-5
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=1,5
f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5
8 2 8
2010-03-20T19:52:29+01:00
A) 4x-3=3x+5 / +3
4x=3x+8 / -3x
x=8
b) 5x+2=7-3x/+3x
8x+2=7/-2
8x=5
x=5/8
c) 3(x-1)=0
3x-3=0/+3
3x=3
x=1
d)-6(x+1)=24
-6x-6=24/+6
-6x=30
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1/+7x
14=10x-1/+1
15=10x
1,5=x
f)4(x-1)=6(1+x)
4x-4=6+6x/-4x
-4=6+2x/-6
-10=2x
-5=x
5 5 5